2021
DOI: 10.1590/0034-7167-2020-1244
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with alcohol, tobacco and illicit drug use among Brazilian undergraduate students

Abstract: Objectives: to analyze the factors associated with the use of alcohol, tobacco and illicit drugs among Brazilian undergraduate students. Methods: observational, cross-sectional study, with convenience sampling, conducted in 2014/2015, involving institutional data and a self-completed online questionnaire, analyzed using measures of frequency, central tendency/dispersion and logistic regression. Results: among 126,326 students, 62.8% reported alcohol use; 11%, tobacco; and 7.5%, illicit drugs. Several academ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
1
0
Order By: Relevance
“…Outras drogas, contribuem para a mortalidade mundial, como o uso de tabaco (passivo e ativo), Brazilian Journal of Health Review, Curitiba, v. 6, n. 6, p.32106-32120, nov./dec., 2023 que é responsável por aproximadamente 6 milhões de mortes anualmente (12). Além disso, o tipo de droga exerce grande influência, tendo em vista que algumas substâncias causam maior dependência química do que outras, gerando maior resistência a terapia (13).…”
Section: Introductionunclassified
“…Outras drogas, contribuem para a mortalidade mundial, como o uso de tabaco (passivo e ativo), Brazilian Journal of Health Review, Curitiba, v. 6, n. 6, p.32106-32120, nov./dec., 2023 que é responsável por aproximadamente 6 milhões de mortes anualmente (12). Além disso, o tipo de droga exerce grande influência, tendo em vista que algumas substâncias causam maior dependência química do que outras, gerando maior resistência a terapia (13).…”
Section: Introductionunclassified
“…Although some studies have analyzed alcohol consumption in students in the health area (Baumgarten et al, 2012; Freire et al, 2020; Pelicioli et al, 2017; Pires et al, 2020; Rodríguez-Muñoz et al, 2020), few studies have compared this consumption between areas of knowledge and observed a higher prevalence in students from other areas when compared with the health area (Brazil. National Secretariat for Drug Policies, 2010; Simplício et al, 2021). We hypothesize that the abusive consumption of alcoholic beverages is greater among students in other areas (including courses in the areas of mathematics, science, and humanities) and that the associations with sociodemographic and behavioral factors are stronger in these students when compared with those in the health area.…”
mentioning
confidence: 99%